EKSISTENSI LEMBAGA NEGARA DALAM PENEGAKAN HAK ASASI MANUSIA DI INDONESIA - Muhammad Amin Putra (Fiat Justisia: Jurnal Ilmu Hukum, 2015)
In the framework of the protection and enforcement of Human Rights by state institutions among implemented by: National Commission on Human Rights, Indonesian Child Protection Commission, National Commission for Women, the Truth and Reconciliation Commission, but the Truth and Reconciliation Commission in its development, it was disbanded because it does not correspond to the actual functions and duties so it does not give justice to the community. Besides carried out by the Commission, established by the State, protection and enforcement of Human Rights today is mostly done by the judiciary, especially after the reform. Among them are: the Specific Human Rights court, severe Human Rights court and the Constitutional Court who has the authority to test Legislations on the Constitution 1945. In the development, the Constitutional Court more precisely to the protection and enforcement of Human Rights to the citizens with the many rulings on the legislation is unconstitutional, and the Constitutional Court's decision was a strategic value and is able to uphold Human Rights for citizens. The essence of the protection and enforcement of Human Rights greatly influenced the position of the judge in deciding the case, so the judge has a role to uphold the independence and impartiality both as an institution and as individuals. Besides other factor is their right to receive legal aid, the pattern of justice has shown that the right to get a legal assistance is an attempt for equality in law as part of the fulfillment of Human Rights.Keywords: State Institutions, Human Rights, Enforcement